164k views
4 votes
Solve -6r-9(-6r-2)=3r+9(5r+7)

2 Answers

1 vote
Use the app Photomath it helps a lot
User Trantor
by
5.9k points
5 votes

First, we need to get rid of the parenthesis from -6r-9(-6r-2) = 3r+9(5r+7):

-9(-6r-2) = 54r+18.

9(5r+7) = 45r+63.

If we substitute the new expressions in, we would get:

6r+54r+18 = 3r+45r+63.

Then, we combine like terms:

60r+18 = 48r+63

We subtract 48r from both sides:

60r+18-48r = 48r-48r+63

12r+18 = 63

Then, we subtract 18 from both sides:

12r+18-18 = 63-18

12r = 45

In order to completely isoslate r, we need to divide both sides by 12:

r = 45/12 = 3 3/4

User Aleph
by
6.5k points